The Effect of Diaphragm Breathing Exercise To Lower Back Pain Changes of Pregnant Women in Tapa Public Health Center, Bone Bolango District - Rabia Zakaria; Magdalena M. Tompunuh; Hasnawatty S. Porouw (Health Notions, 2019)
Low back pain to pregnancy is described as a pain in lumar region, on the sacrum, and can up to the feet. The pain is intermitte, and aggravated by doing activities with the same position in a long time, usually happens in 30 minutes like walking, sitting, and standing. If not handled well, bottom pain will disturb the activities of pregnant women so that it will make the life quality of pregnant women become bad. Diaphragm breathing exercise help the patients to use diaphragm well while breathing. The research type was pre-experimental design, with the design of One Group Pretest-posttest Design. The population of this research were all pregnant women located in the working area of Tapa Public Health Center. Population size were 40 people. Sample size was obtained from total population that were chosen by using purposive sampling technique. The sample size was determined by using Slovin formula which obtains 16 Respondents who fulfill Inclusion and exclusion criteria, the statistical test was by normality test using Shapiro Wilk Test. The results was that 75% respondents who suffer mild pain and 12.5% respondents who suffer moderate pain and there was an effect of giving diaphragm breathing exercise practice to changes in lower back pain to Pregnant women with p value 0.000. Expected able to enhance the society’s knowledge especially pregnant women about diaphragm breathing exercise implementation instructions in pressing the changes of lower back pain. Keywords: Diaphragm breathing, Pregnant, Lower back pain